SKOVORODINSKIJ TRADITIONS IN THE ACTIVITY OF THE HEADS OF THE PEDAGOGICAL DEPARTMENT OF THE KHSPI (30-IES OF THE XX CENTURY) - Башкір, О.; Золотухіна, С. (New Collegium, 2020)
The article focuses of the relevance of H. S. Skovoroda’s ideas (for instance, the ideas of related work, critical thinking and moral wisdom) throughout the development of pedagogical science and society. it has been noted in the article that the educator and wandering philosopher’s educational ideas formed the basis of worldview and activities of the heads of the Department of Pedagogy at Kharkiv State Pedagogi- cal institute in the 1930s. T. P. Harbuz, i. i. Sinepоl and S. A. Lytvynov were these heads. in the context of H. S. Skovoroda’s philosophy, the peculiarities of the content and the directions of their activities in this important and difficult period of the development of the country have been determined and revealed. Taking into account the insufficient study of the mentioned personalities, the article depicts their contribution to the development of pedagogical science and organizational-pedagogical foundations of the work of the Department of Pedagogy.